Developing an Indigenous Surgical Workforce for Australasia. Issue 12 (12th August 2013) - Aramoana, Jaclyn; Alley, Patrick; Koea, Jonathan B.
Abstract Background Progress has been made in Australia and New Zealand to increase the numbers of indigenous students (Aboriginal, Torres Strait Islander and Maori) entering primary medical qualification courses. In New Zealand, up to 20 Maori are graduating annually, with similar numbers possible in Australia, creating a potential opportunity to develop an indigenous surgical workforce. Methods A literature review identified factors utilized by medical schools to attract indigenous students into medical careers and the interventions necessary to ensure successful graduation. A further search identified those factors important in encouraging indigenous medical graduates to enter specialist training programmes and achieve faculty appointments. Results All medical schools have utilized elements of a 'pipeline approach' encompassing contact with students at secondary school level to encourage aspirational goals and assist with suitable subject selection. Bridging courses can ensure students leaving school have appropriate skill sets before entering medical degree courses. Extensive practical help is available during primary medical qualification study. The elements necessary for primary medical qualification success – dedicated and focused study, developing appropriate skill sets, mentoring, support, and an institutional and collegial commitment to success – are also the elements required for postgraduate achievement. Conclusion The Royal Australasian College of Surgeons (RACS) is primarily involved in training rather than service provision. The increasing numbers of indigenous medical graduates in both Australia and New Zealand represent an opportunity for the College to contribute to improving indigenous health status by implementing specific measures to increase numbers of indigenous surgeons.